The Anti-proliferative Effect of a Novel Glutaminase Inhibitor IN-3 on Prostate Cancer Cells - Ummuhan DEMIR; Ayse Busranur CELIK (Medeniyet Medical Journal)
Objective: This study aimed to evaluate anti-cancer potential of a novel glutaminase (GLS) inhibitor IN-3 in prostate cancer cells. Methods: The cell viability upon IN-3 treatment was examined using crystal violet staining and IC50 values were calculated for cancer cell lines PC-3 and LNCaP and normal fibroblasts CCD1072sk. The expression levels of GLS isoforms were determined by real-time polymerase chain reaction after IN-3 treatment. The metastatic prostate cancer dataset was downloaded from C-Bioportal and the expressions of GLS isoforms were analyzed. Results: The IC50 values of IN-3 for LNCaP, PC-3 and CCD1072sk were 2.13, 6.14 and 15.39 μM respectively. The dose dependent effect of IN-3 was evident even in low concentration with 1 μM in LNCaP and 2 μM in PC-3 and these anti-proliferative effects of IN-3 were highly significant with p-values lower than 0.0001. The treatment of PC-3 cells with 10 μM IN-3 elevated the expression of kidney type GLS isoform of GLS1 but not GLS2. Comparison of metastatic and localized prostate cancer tissues showed that GLS1 was highly expressed not only in primary but also in metastatic prostate cancer tissues. GLS1 expression was significantly higher than GLS2 expression with p-values lower than 0.001. Conclusions: The GLS inhibitor IN-3 may be a potent anti-cancer agent in prostate cancer by demonstrating its differential effect between cancer and normal cells. Further studies are warranted to elucidate its drug potential in prostate cancer.